In the Language of Schoemperlen - Whetter, Darryl (Studies in Canadian Literature, 1996)
Fiction writer Diane Schoemperlen discusses her novel In the Language of Love, with Darryl Whetter focussing on the importance of form, structure, character, and gender, as well as the effect that motherhood had on her writing of the book. Truth, memory and story, along with the idea of the writer as a liar are also discussed, as are thoughts on writing and the novel by writers such as Kundera, Woolf, and Kroetsch. Schoemperlen also comments on the experience of writing a novel versus writing other forms of fiction, and on her place in the Canadian writing community.